Enhancing Students Critical Thinking Skills through Pancasila Student Profile Strengthening Project at SMK Negeri 3 Yogyakarta - Anang Estu Pribadi; Marzuki Marzuki (PT Publikasiku Academic Solution, 2024)
This research aims to: 1) Analyze the implementation of the Pancasila Student Profile Project in strengthening the critical thinking character of students; and 2) analyze the inhibiting factors in the implementation of the Pancasila Learner Profile Strengthening Project in strengthening the critical thinking character of students at SMK Negeri 3 Yogyakarta. This research deploys a qualitative research approach with a case study method. The purposeful sampling technique is used in recruiting research participants, and the data collection strategy encompasses observations, interviews, and documentation. The data gathered is validated through triangulation techniques and multiple-source triangulation. The data gathered is analyzed using Miles and Huberman’s models of data reduction, data presentation, and conclusion drawing. The results of this study show: 1) the implementation of the Pancasila Student Profile Strengthening Project (P5) in strengthening the character of critical thinking is integrated with the use of project-based and problem-based learning methods in P5 comprehensive themes. The combination of learning from all themes can develop students’ skills in critical citizenship characteristics; and 2) P5 implementation, internal and external obstacles are miscommunications affecting coordination and implementation. These miscommunications are caused by various factors. Thus, increasing awareness and strong collaboration among each school element are crucial.